A Patient 84 Years Old with Chronic Inflammatory Diarrhea Mild to Moderate Dehydration et Causa Ulcerative Pancolitis - Syarifa, Yulia; Effiyana, Arika; Ulfah, Maria (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2024)
Background: Ulcerative pancolitis is a chronic Inflammatory Bowel Disease (IBD) characterized by superficial mucosal ulceration, rectal bleeding, diarrhea, and abdominal pain. Unlike Crohn's disease, Ulcerative pancolitis is limited to the colon and involves inflammation confined to the mucosal layer. Ulcerative pancolitis affects the colon in a retrograde manner starting from the rectum and extending proximally. The most dominant clinical symptoms in patients with Ulcerative pancolitis are abdominal pain and diarrhea accompanied by bleeding. Additionally, other symptoms can include anemia, fatigue, weight loss, rectal bleeding, loss of appetite, dehydration, malnutrition, skin lesions, joint inflammation, and impaired growth.Purpose: This study aims to reported of a Patient 84 Years Old with Chronic Inflammatory Diarrhea Mild to Moderate Dehydration et causa Ulcerative pancolitis  Case Presentation: A male patient, 84 years old, was admitted to Ulin Hospital Banjarmasin on March 8, 2024, with the diagnosis of chronic inflammatory diarrhea with mild to moderate dehydration, ulcerative pancolitis, leukocytosis, leukocyturia, erythrocyturia, mild anemia, elevated liver, BPH, Candidiasis oral, and Geriatric problem (inanition, immobility, infection, frailty)Conclusion: This case highlights the complex clinical presentation of chronic inflammatory bowel disease in the elderly population, often complicated by multiple comorbidities. A comprehensive approach to diagnosis and management is essential to optimize patient outcomes.Keywords: Ulcerative pancolitis, IBD, diarrhea, geriatric